A STUDY ON THE READING ABILITY OF THE FIRST YEAR STUDENTS OF MTs DARUL HIKMAH PEKANBARU IN COMPREHENDING DESCRIPTIVE TEXTS - Lestari, Fitri; Azhar, Fadly; Masyhur, Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is aimed to find out the reading ability of the first year students of MTs Darul Hikmah Pekanbaru. The population of this research is the first year students of MTs Darul Hikmah Pekanbaru. The number of sample is 36 students selected by using cluster random sampling technique. The instrument to collect the data was multiple choice test items with 30 questions. . Each text consist of 5 questions which cover the components of reading and the components of descriptive that is finding main ideas, finding factual information, finding meaning of difficult word, finding reference, and finding inference. The data were analyzed by classifying them into five levels of mastery, such as very poor, very poor to poor, poor to mediocre, mediocre to good and good to excellent. Based on the findings this research, it was found that the students’ reading ability of the first year students of MTs Darul Hikmah Pekanbaru was in good level with the mean score was 66.91. The implication of this research is that the first year students of MTs Darul Hikmah Pekanbaru have a good ability in reading descriptice text.Key Words: Students’ ability, Reading, Descriptive Text